The Facts About Time : To-Build - Koeva Brooks, Petya (IMF Working Papers; Working Paper ;, 2000)
This paper presents new empirical evidence about the process of plant investment. Using newspaper and trade journal articles, the author collects and analyzes time-to-build data for a sample of Compustat firms. These data suggest that the average construction lead time for new plants is around two years in most industries. Business cycle fluctuations do not affect the length of time-to-build. The investment lead times are generally not sensitive to the size of the projects. Only nine percent of the firms in the sample deviate from their investment schedules and delay or abandon their projects.